Case Study of Samsung’s Mobile Phone Business - Lee, Boon-Young; Lee, Seung Joo (KDI School of Public Policy and Management, 2004)
This paper examines Samsung Electronics successful growth strategy in the mobile phone business. It examines its early efforts at developing a competitive product in the domestic market, its globalization strategies, and some of the key challenges it faces today. The paper provide insights into how a late-comer to an industry can overcome certain disadvantages and successfully position itself as a widely respected and successful brand.
Keywords: Samsung; mobile phone; strategy